Analysis of rationalization through restructuring of Islamic finance based on the Ihsan principle - Erfan Asmaie Khairul Anam,; Abdul Basir Mohamad,; Mohammad Zaini Yahaya, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Ihsan is the pursuit of excellence in worship and daily activities to achieve success and happiness so as to be rewarded with sweetness of faith and Paradise for doing something beyond what is required. A person who does not pursue ihsan is not considered as zalim (wrongful or unjust) or failing his religious obligations as long as he is just and fair. The main goal of Islamic banking institutions is to avoid all forms of zulm (injustice, cruelty, oppression, exploitation) in transactions and to distinguish Islamic transactions from conventional financial practices. In order to ensure quality and harmony, muamalat practice must be assessed and reviewed from the perspective of ihsan to gain the blessings and pleasure of Allah SWT. The purpose of this study is to analyze and evaluate the rationalization in restructuring Islamic financing from the perspective of ihsan to ensure the objectives and functions of Islamic financial institutions are achieved. This research is qualitative using the method of content analysis. The data were analyzed using descriptive and deductive methods. The results show that the recommendations from the Central Bank of Malaysia and rationalization of Islamic financing restructuring procedure fulfills the principle of ihsan in past implementation and during the Covid-19 pandemic crisis. Islamic banking institutions have been responsible and exercised forbearance by providing facilities and eliminating difficulties to assist customer dealings. Customers also have the responsibility to banks that have provided financing facilities and accommodated their financial affairs. Hence, this study can serve as a guide to all parties in applying the principle of ihsan to any action and practice to ensure a more meaningful life.